Necessary optimality conditions for minimax programming problems with mathematical constraints. (2nd November 2017) - Bao, Truong Q.; Gupta, Pankaj; Khanh, Phan Q.
Abstract : In this paper, necessary optimality conditions in terms of upper and/or lower subdifferentials of both cost and constraint functions are derived for minimax optimization problems with inequality, equality and geometric constraints in the setting of non-differentiatiable and non-Lipschitz functions in Asplund spaces. Necessary optimality conditions in the fuzzy form are also presented. An application of the fuzzy necessary optimality condition is shown by considering minimax fractional programming problem.